Islam Dan Hak Anak: Tanggung Jawab Keluarga Dan Sekolah Dalam Pembentukan Akhlak Anak Usia Dini - Ahmad Ilham Fadli; Dwi Suci Rahma Putri; Dimas Raba Pramodana; Erlina; Umi Hijriyah; Nirva Diana (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2024)
Morals can reflect personality as well as can describe a character that contains goodness called good morals or noble morals, and contains badness called bad morals or noble morals. Noble morals, and bad morals are called bad morals or despicable morals. Despicable morals. Aiming to provide knowledge to parents and teachers to see the character education that exists in pre-school children before they enter elementary school. Elementary school age. In this case, teachers and parents, especially teachers, play a very important role in strengthening character education for students. Play a role in strengthening character education for their students, where teachers must exemplify what is conveyed and will be imitated by their students. The importance of the role of Islam in the formation of early childhood morals through the responsibility of family and school. Responsibility of family and school. The method used in this research is approach (Library Research). With the results of the research The role of parents and teachers in realising Islamic character has a reciprocal relationship. Islamic character has a reciprocal relationship. Family as the basis for initial formation while the school as a complement to children's character education